Educação do campo e práticas ambientais sustentáveis : um olhar para o PROJOVEM Campo Saberes da Terra em Pedra Mole/SE - Santos, Juniela (2019)
ProJovem Campo Saberes da Terra is a Federal Government Program aimed at schooling and initial professional qualification in Rural Family Production of young family farmers in the age group of 18 to 29 years old. The research deals with the environmental practices highlighted by the program, considering its relevance in the construction of a basic theoretical, conceptual and empirical framework for the critical reading of the world and the effects of the "Green Revolution" and the technological package for family agriculture. In the municipality of Pedra Mole, the health of soil, water, living beings and farmers is compromised due to the abusive use of agrochemicals, as well as their production space is being undermined by machines as well as transgenic crops. Despite its relevance to the resumption of agroecological paradigms, the research problem arises from the fact that the program is not configured as an effective and permanent educational public policy of the Field. With this, the objective was to analyze how the educational policies of the Field are being carried out, taking as reference the State of Sergipe; the specific objectives were: to understand the man-nature relationship from the modernization conducted by the State to the rural space; to present the concept of Field Education and its effectiveness for a sustainable rural area; to analyze the realization and the contradictions of the Projovem Campo Saberes da Terra. In Sergipe, this program was in its third performance (2015/2017). The research locus was the municipality of Pedra Mole, located in the western sertão of Sergipe. The methodology of this study was subsidized by bibliographical, documentary, field research and questionnaire application with the students of Projovem Field in the municipality of the research locus also of interviews with other key actors (rural workers, secretary of education and agriculture of the municipality Pedra Mole, Coordinator of the Field Education Center of Sergipe, and Coordinator of the EJA Field of the Municipality of Simão Dias). It was hoped to discuss the importance of the program as an educational public policy as a structural alternative for the social subjects of the field to appropriate the socio-environmental knowledge necessary to confront the current model of agricultural development, shaped by agribusiness, transgenics and agrochemicals and towards the development of a healthy life. However, it was observed the lack of effectiveness of the program, since it is configured as an education policy of the punctual and compensatory field. This fact calls into question the relevance of the program in the face of the need for emancipatory public policies for the subjects of the countryside.